INTERNALISASI NILAI-NILAI ASWAJA DALAM PEMBELAJARAN PAI PADA GENERASI Z STUDI KASUS SMA ISLAM AL MAARIF SINGOSARI - Ubaidatus Sholihah; Anwar Sa’dullah; Indhra Mustofha (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This research discusses the internalization of Aswaja values in PAI learning inGeneration Z at Al Maarif Singosari Islamic High School, Malang Regency. The purposeof this research is to determine what Aswaja values are and how the process ofinternalizing these values in PAI learning in Generation Z works. The focus of theresearch used among others aspect; how to internalize Aswaja values, the relationshipbetween Aswaja values and PAI, and inhibiting variables Internalization of theseAswaja values. This research uses a qualitative approach and using the case studymethod. The data sources were provided by the school principal, PAI teachers, andAswaja teachers. Data was collected through three methods: 1) Interview, 2)Documentation, and 3) Observation. The results of this research show that Al MaarifIslamic High School internalizes five Aswaja values: Tasamuh (tolerance), Tawazun(balance), Tawasuth (moderate), Ta’adul (fair and neutral) and amar ma'ruf nahimunkar. Implemented by PAI teachers through 3 phase: 1) Value transformationphase, 2) Value transaction phase, and 3) Trans-internalization phase. And theinternalization process has obstacles, one of which is caused by cyber crime